2012
DOI: 10.2176/nmc.52.175
|View full text |Cite
|
Sign up to set email alerts
|

Medical Care for Chronic-Phase Stroke in Japan

Abstract: Stroke leaves serious neurological sequelae, which require long-term medical and social care, imposing financial and mental burdens on the patients and their families, and causing enormous losses to society. It is currently required that medical resources be used efficiently and the cost-effectiveness of treatment be analyzed carefully. We conducted a follow-up survey of stroke patients admitted to the hospital attached to our university in order to build a picture of the current status of chronic-phase stroke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 15 publications
0
30
0
Order By: Relevance
“…First, we did not use Japan-specific utility data except for chronic phase stroke because of a lack of utility data for some event states. 16 In addition, as mentioned above, the utility values of severe stroke in the Japanese model were significantly lower than those in the original model, but the reason for the difference is unknown because of a lack of data, such as a country comparative study using the EQ-5D for stroke. Sakthong et al reported that the difference in utility values of type 2 diabetes mellitus was observed between the preference weights in the United Kingdom, United States, and Japan, revealing higher scores in the United States than in the United Kingdom and Japan.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…First, we did not use Japan-specific utility data except for chronic phase stroke because of a lack of utility data for some event states. 16 In addition, as mentioned above, the utility values of severe stroke in the Japanese model were significantly lower than those in the original model, but the reason for the difference is unknown because of a lack of data, such as a country comparative study using the EQ-5D for stroke. Sakthong et al reported that the difference in utility values of type 2 diabetes mellitus was observed between the preference weights in the United Kingdom, United States, and Japan, revealing higher scores in the United States than in the United Kingdom and Japan.…”
Section: Discussionmentioning
confidence: 96%
“…The costs of chronic stroke were obtained from the study by Hattori et al, which included not only direct medical cost but also the long-term care cost. 16 The cardiogenic brain embolism data derived from Stroke Data Bank 2009 were used for distribution of the mRS scores for each stroke severity in Japanese patients. 17 The cost of medication therapy and that of percutaneous coronary intervention for the chronic phase of MI are quoted from the report of Tanihata et al 18 The percentage of patients receiving each treatment was obtained from a study using claims data analysis in Japan by Evans et al 19 Because the research by Tanihata et al was conducted in 2001, the cost derived from the study was adjusted to 2014 rates based on the revised total medical treatment fees thereafter (Tables VI and VII).…”
Section: Localizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment costs were mainly obtained from cost parameters used by Kamae et al who evaluated the costeffectiveness of apixaban compared to warfarin for stroke prevention in Japanese NVAF patients 27 . In this study, two main sources of event treatment costs were used: the Medical Data Vision Co Ltd (MDV) database analysis by Kamae et al, which provided the actual costs of a stroke, bleedings, MI and SE from admission until discharge 27 , and a follow-up survey of Japanese stroke patients admitted to a university hospital conducted by Hattori et al, which provided the utility and medical costs at one year after onset 28 .…”
Section: Resource Use and Costsmentioning
confidence: 99%
“…It can be due to ischemia or hemorrhage, and individuals are often left with serious sequelae requiring long-term medical treatment. 1 Stroke patients often experience medical distress, and the therapeutic objective has shifted from bringing about a cure or prolonging life only to comprehensive treatment that includes improving the quality of life (QOL). 2 In its original meaning, QOL was clearly related to the subjective perception of emotions such as satisfaction and happiness.…”
mentioning
confidence: 99%